Analyzing Occupations in Order to Change Human’s Behaviors and Habits - Marquez-Lanza, Francisco Jesus (My University, 2019)
Through clinical experience, observation, and analysis of everyday occupations, specifically the basic one, occupational therapy practitioners are key to get any change in human behaviors or maladaptive habits. By changing or adapting daily activities and transforming them into adjusting habits we can help our clients change their behaviors and thinking. The future of our OT profession is to investigate, educate, and intervene in the basic “Everyday Occupations” because OT practitioners have the knowledge and the training to intervene in populations with different background and cultures
Llevamos también un poster.
Keywords: Terapia ocupacional; Occupational Therapy; Human’s Behaviors; Habits